Resahaping Global Trade throudh Sustainable E-commerce Ecosystems (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This paper analyzing how reshaping the future of global trade, explore the transition from traditional online retail models toward sustainable e-commerce ecosystems. By examining the integration of circular economy principles, green logistics, and ethical supply chain manajement, the study identifies the core drivers behind this transformation